2012
DOI: 10.3390/molecules171112636
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Phenolic Compounds from the Rhizomes of Cyperus rotundus L.

Abstract: Two novel compounds, 1α-methoxy-3β-hydroxy-4α-(3′,4′-dihydroxyphenyl)-1, 2,3,4-tetrahydronaphthalin (1) and 1α,3β-dihydroxy-4α-(3′,4′-dihydroxyphenyl)-1,2,3,4-tetrahydronaphthalin (2), were isolated along with six known compounds 3–8 from the rhizomes of Cyperus rotundus. This paper reports the isolation and full spectroscopic characterization of these new compounds by NMR, UV, IR and MS data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Our finding was in agreement with the reported antioxidant (Yazdanparast and Ardestani, 2007) and hepatoprotective efficacy of C. Rotundus total extract in CCl 4 -induced hepatic injury in rats (Gilani and Janbaz, 1995, Mohamed, 2015). The observed hepatoprotective effect of C. rotundus against DCFH-cytotoxicity can be attributed to the presence of flavonoids and related phenolic compounds which are well known as antioxidants and free radical scavengers (Sunil et al, 2011, Zhou and Yin, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding was in agreement with the reported antioxidant (Yazdanparast and Ardestani, 2007) and hepatoprotective efficacy of C. Rotundus total extract in CCl 4 -induced hepatic injury in rats (Gilani and Janbaz, 1995, Mohamed, 2015). The observed hepatoprotective effect of C. rotundus against DCFH-cytotoxicity can be attributed to the presence of flavonoids and related phenolic compounds which are well known as antioxidants and free radical scavengers (Sunil et al, 2011, Zhou and Yin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…C. rotundus extracts are reported to have several biological activities like, anti-inflammatory (Tandon et al, 2010), in vivo hepatoprotective (Gilani and Janbaz, 1995), antimalarial (Thebtaranonth et al, 1995, Rukunga et al, 2008), antidiarrhoeal (Uddin et al, 2006), antioxidant (Yazdanparast and Ardestani, 2007) antimicrobial (Chen et al, 2011), antiplatelet (Seo et al, 2011), neuroprotective (Kumar et al, 2013), anti-hyperglycemic and anti-nociceptive (Alam et al, 2011, Chaulya et al, 2011). Previous phytochemical screening of C. rotundus showed that it contains many phytoconstituents including flavonoids (Sunil et al, 2011), alkaloids (Sayed et al, 2008) and polyphenols (Zhou and Yin, 2012, Dhillon et al, 1993). Moreover, eight sesquiterpenes, nootkatone, valencene epi-guaidiol, sugebiol, guaidiolA, sugetriol triacetate, cyperenoic acid and cyperotundone were isolated from its rhizomes (Thebtaranonth et al, 1995, Dhillon et al, 1993, Jin et al, 2011, Xu et al, 2009, Tsoyi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The distinct smell of teki is originated from the essential oil which is a volatile component giving the peculiar smell of teki (Mohamed, 2015). Such compound are for example cineole, cyperene, cyperenone, cyperol, cyprerotundone, limonene (Zhou and Yin, 2012). This research used the other materials which are strawberry, pineapple, and soursop that can fix the taste and smell.…”
Section: The Organoleptic Test Of the Functional Beverage Of The Extrmentioning
confidence: 99%
“…[ 58 ] The rhizomes are also the source of two new phenolics, 1alpha-methoxy -3beta - hydroxy-4alpha (3′,4′-dihydroxyphenyl)-1,2,3,4-tetrahydronaphthalene and its demethylated parent. [ 59 ]…”
Section: Phytochemistrymentioning
confidence: 99%